Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\frac{2}{3}+x\right)\left(\frac{1}{5}-2x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\frac{2}{3}+x=0\\\frac{1}{5}-2x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{2}{3}\\-2x=-\frac{1}{5}\end{cases}\Leftrightarrow}}\orbr{\begin{cases}x=-\frac{2}{3}\\x=\frac{1}{10}\end{cases}}\)
Vậy:.......
#H
(2/3×x-1/3)=2/3+1/3
(2/3×x-1/3)=3/3
2/3×x=3/3+1/3
2/3×x=4/3
x=4/3:3/2
x=4/3×2/3
x=8/9
\(\frac{17-x}{1+\frac{1}{2}}=1-\frac{1}{12}.x=>\frac{17-x}{\frac{3}{2}}=1-\frac{1}{12}.x=>\frac{\left(17-x\right).2}{3}=1-\frac{1}{12}.x\)
\(=>\left(17-x\right).2=\left(1-\frac{1}{12}.x\right).3=>34-2x=3-\frac{1}{4}x\)
\(=>34-2x-3+\frac{1}{4}x=0=>-\frac{7}{4}x+31=0=>-\frac{7}{4}x=-31=>x=\left(-31\right):\left(-\frac{7}{4}\right)=\frac{124}{7}\)
Bài 1:
\(\frac{7}{12}+\frac{-8}{15}=\frac{7}{12}-\frac{8}{15}=\frac{35}{60}-\frac{32}{60}=\frac{3}{60}=\frac{1}{20}\)
\(\frac{5}{12}+\frac{-8}{15}=\frac{5}{12}-\frac{8}{15}=\frac{25}{60}-\frac{32}{60}=\frac{-7}{60}\)
Bài 2:
\(a,x-23=-56\)
\(x=-56+23\)
\(x=-33\)
\(b,2x-36=24\)
\(2x=60\)
\(x=30\)
\(c,x-\frac{4}{5}=\frac{3}{2}\)
\(x=\frac{3}{2}+\frac{4}{5}=\frac{23}{10}\)
\(d,x-46=123\)
\(x=123+46=169\)
\(e,2x-25=-45\)
\(2x=-20\)
\(x=-10\)
\(f,x-\frac{2}{3}=-\frac{7}{5}\)
\(x=-\frac{7}{5}+\frac{2}{3}=-\frac{11}{15}\)
=.= hk tốt!!
* \(\left(x-\frac{5}{24}\right)\cdot\frac{18}{7}=-\frac{12}{7}\)
<=> \(x-\frac{5}{24}=-\frac{2}{3}\)
<=> \(x=-\frac{11}{24}\)
* \(\frac{3}{4}+\frac{1}{4}\left(x-1\right)=\frac{1}{2}\)
<=> \(\frac{x-1}{4}=\frac{-1}{4}\)
<=> \(x-1=-1\)
<=> \(x=0\)
* \(\left(4x-\frac{1}{2}\right)\left(\frac{x}{3}-\frac{1}{5}\right)=0\)
<=> \(\orbr{\begin{cases}4x-\frac{1}{2}=0\\\frac{x}{3}-\frac{1}{5}=0\end{cases}}\)<=> \(\orbr{\begin{cases}4x=\frac{1}{2}\\\frac{x}{3}=\frac{1}{5}\end{cases}}\)<=> \(\orbr{\begin{cases}x=\frac{1}{8}\\x=\frac{3}{5}\end{cases}}\)
\(\frac{2}{3}.x-\frac{1}{2}.x=\frac{5}{12}+x\)
\(\Rightarrow\frac{2}{3}.x-\frac{1}{2}.x-x=\frac{5}{12}\)
\(x.\left(\frac{2}{3}-\frac{1}{2}-1\right)=\frac{5}{12}\)
\(x.\left(\frac{-5}{6}\right)=\frac{5}{12}\)
\(x=\frac{5}{12}:\left(\frac{-5}{6}\right)\)
\(x=\frac{-1}{2}\)